Is there an aesthetics of political song? - Guerreiro, Vítor (2021)
Some think politics and art should not mix. The problem with this view is that politics and art were always entwined. Human experience is structured politically, even if much of it is not. Here, I illustrate this with a series of artistic examples that take us from work songs in a Mississippi 1940s forced labour camp to a desolate dead forest landscape in a former Krasnoyarsk gulag, evocative of a Paul Nash World War I painting. Powerful artworks help us to come to grips with human experience, more than merely "expressing emotion". I treat songs as representations, looking for a way their political significance is part of their aesthetic value. To do this, I defend James Young's (2001) concept of "illustrative representation" as bridging the gap between formalism and contextualism. But instead of Young's "Wollheimian" (resemblance between experiences) approach to how such representation works I draw on Kulvicki's (2020) notion of "syntactic parts", combining it with Carroll's (2016) concept of form as the "ensemble of artistic choices", and Black's (1954-55) frame-and-focus model of meaning in metaphor. Hopefully, in the end I will have clarified the ways in which (some) songs are both politically and aesthetically meaningful.